(untitled) (Revista Apotheke, 2022)
The article was developed during a scientific research scholarship, linked to the project "The painting studio as a teaching and learning laboratory in visual arts”, by Prof.ª Dr.ª Jociele Lampert, at the University of the State of Santa Catarina (UDESC). The research approaches the manufacture of paints and how it contributes to the training of artist teachers, for their processes in visual arts and for the process of creating classes at school. For the study, the use of earth pigments in the work of the artist Silvia Carvalho was investigated, practical studies were carried out on how to make paints with the earth pigments and the use of these pigments in the Graduation courses in Visual Arts.